Underneath the Bragg peaks structural analysis of complex materials - Egami, Takeshi; Billinge, Simon J. L. (Pergamon, an imprint of Elsevier, 2012)
This book focuses on the structural determination of crystalline solids with extensive disorder. Well-established methods exist for characterizing the structure of fully crystalline solids or fully disordered materials such as liquids and glasses, but there is a dearth of techniques for the cases in-between, crystalline solids with internal atomic and nanometer scale disorder. Egami and Billinge discuss how to fill the gap using modern tools of structural characterization. This problem is encountered in the structural characterization of a surprisingly wide range of complex materials of interest to modern technology and is becoming increasingly important. Takeshi Egami received the 2003 Eugene Bertram Warren Diffraction Physics Award for the work described in the book. The authors received 2010 J. D. Hanawalt Award from the International Union of Crystallography largely based on the success of this book Praise for the first edition:Egami and Billinge are experts in the application of PDF analysis and their writing is both clear and insightful. The organisation of the book is also excellent, with illuminating examples provided throughout. If you have an interest in atomic structure of materials, and local structural details in particular, PDF methods can be profoundly useful. I would heartily recommend this book as a starting point if you are considering using PDF analysis in your own work. For more experienced practitioners, this text is a useful reference. Materials Today, June 2004 Introduces a unique method to study the atomic structure of nanomaterialsLays out the basic theory and methods of this important emerging techniqueThe first edition is considered the seminal text on the subject
Keywords: Composite materials -- Analysis; Nanostructured materials -- Analysis; Crystallography; Solids -- Analysis; Kristallstrukturanalyse; Gitterbaufehler; Amorpher Festkörper; Electronic books